Scientific popular journalism in Belarus: historical aspect - Tychko, Hаlina K. (Journal of the Belarusian State University. Journalism, 2023)
The necessity of researching the history of the formation of national scientific popular journalism is substantiated. The origins of the scientific popular direction of the Polish-language press in Belarus in the 19th century are considered. Based on the analysis of the editorial and publishing activities of I. Lelevel and A. G. Kirkor, the problematic and genre-thematic orientation of publications of a scientific and popular character is determined. Conclusions are made about the mutual influence and interdependence of socio-public value and aesthetic dominants and functional and aesthetic parameters of the press.
Keywords: scientific popular journalism; scientific magazine; readership; author’s assets; educational traditions; genre palette; thematic diversity; functional purpose